EFEKTIVITAS PENERAPAN SISTEM DAN PROSEDUR AKUNTANSI AKTIVA TETAP BERDASARKAN PSAK 16 TAHUN 2011 DALAM EKONOMI SYARIAH - Risna Nurhaida Hafni; Ruhadi Ruhadi; Rizky Maidan Ilmi (JURNAL EKONOMI SYARIAH, 2019)
Today, the development of industry 4.0 is pushing for faster and faster development growth. Therefore, the role played in managing fixed assets in a company is very important in order to support the safety of the company in planning, procuring, and maintaining assets properly. Therefore, decision makers in maintaining fixed assets require expertise and policies specifically regarding financial accounting. The research method used in this research is a qualitative descriptive method, data collection is done by combining theories from various sources. In this study aims to determine the use of fixed assets based on PSAK 16 of 2011 in Islamic Economics. The results of this study are expected to be an additional value in the science reference related to Islamic economics. The findings in this study that the use of fixed assets that refer to PSAK 16 of 2011 is a revision of PSAK 16 of 2007, where the use of sharia accounting regarding fixed assets that are used still in conventional accounting. This is expected to have an adequate Islamic economic instrument as a sign that it is important to build a strong economic system based on the Koran and the Sunnah.